The role of BRCA1 and BRCA2 mutations in prostate, pancreatic and stomach cancers - Cavanagh, Helen (Hered Cancer Clin Pract, 2015)
The association of germline mutations in the breast cancer susceptibility gene 1 (BRCA1) and the breast cancer susceptibility gene 2 (BRCA2) with the development of breast and ovarian cancers have been widely researched and recognised. It is known that these genes function at multiple sites in the body. Research has subsequently evolved into the connection of BRCA1/2 with cancers at other sites within the body. This review examines the association of BRCA1/2 germline gene mutations with prostate, pancreatic and stomach cancers. An extensive literature search revealed conflicting findings regarding the association of BRCA1/2 gene mutations with these cancers. Most studies suggest that there is an association between BRCA1/2 mutations and carcinoma of the prostate, pancreas and stomach, but some reports propose that such a correlation may be due to factors other than possessing a mutated BRCA1/2 gene, and other associations may be revealed as further epidemiological information becomes available. The review concludes that as more knowledge arises about the mechanisms of BRCA1/2 gene mutations, it should pave the way for future screening programmes to be applied effectively.